Multiple lifestyle interventions reverses hypertension - Albert Sanchez (Cogent Medicine, 2019)
Hypertension is worldwide and the most common problem in clinical practice in the United States. It is typically treated with medications, but it also responds to various lifestyle principles. This study assessed the effectiveness of reversing hypertension using a multi-lifestyle medical residential intervention. We evaluated retrospective data from the pretest-posttest intervention of the 114 subjects that were hypertensive from among all 173 enrolled in NEWSTART during 2014. Of the 114 individuals with hypertension, there were 37% males and 63% females. Baseline values (Mean±SD) were: 66.5 ± 10.6 years, 31.9 ± 6.6 kg/m2, and 139 ± 20 mmHg. Systolic blood pressure decreased significantly (p < 0.001) within 14 days in all population sub-groups from −8% (diabetic) to −31% (normal weight). Forty percent of subjects achieved <120 mmHg. Medications were discontinued or decreased by 93% of the subjects. This lifestyle intervention is appropriate for first-line treatment of hypertension.